Zura, Zurea : 1. Kapitulua: Esku-erremintak - García, Jorge; Manzaneda, José ([Zornotza] : Izarbel, 1997)
U-matic
EIMA 1996
Keywords: Teknologia; Tailerra; Zurgintza; EIMAk onetsitako materialak; Bideo didaktikoak